Excess Volatility in the Government Debt Market : Evidence from ASEAN-5 - Wong, Shao Jye (2016)
In recent years, sovereign bond prices within the ASEAN-5 region have shown high price fluctuations. Adding to the fact that there is scarce literature in the research of excess volatility in the sovereign bonds of the region, the current study attempts to assess the presence of excess volatility in the sovereign bond markets of the ASEAN-5 countries ; Indonesia, Malaysia, Phillipines, Singapore, and Thailand. The study also attempts to detect excess volatility within the whole region through a panel structure. Fakhry's and Richter's (2015) extension of Shiller's original volatility test is used as it bypasses the need to acquire the rational prices of the bonds. Instead, bond price variances will be modelled using GARCH models to detect excess volatility. Our major findings found the presence of excess volatility in all countries studied in the 10 years and 20 years government bond data. However, panel analysis revealed less evidence of excess volatility and none are detected in the 20 years bond sample. Consequently, these findings suggest that it is possible to mitigate excess volatility by holding government bonds of various countries rather than just holding bonds from a single country that there are benefits from multinational diversification of government bonds. Some measures to reduce the impact of excess volatility in each of the individual countries are also suggested.